Domain Specificity of MAP3K Family Members, MLK and Tak1, for JNK Signaling in Drosophila. Issue 2 (1st June 2014) - Stronach, Beth; Lennox, Ashley L; Garlena, Rebecca A
Abstract: A highly diverse set of protein kinases functions as early responders in the mitogen- and stress-activated protein kinase (MAPK/SAPK) signaling pathways. For instance, humans possess 14 MAPK kinase kinases (MAP3Ks) that activate Jun kinase (JNK) signaling downstream. A major challenge is to decipher the selective and redundant functions of these upstream MAP3Ks. Taking advantage of the relative simplicity of Drosophila melanogaster as a model system, we assessed MAP3K signaling specificity in several JNK-dependent processes during development and stress response. Our approach was to generate molecular chimeras between two MAP3K family members, the mixed lineage kinase, Slpr, and the TGF-β activated kinase, Tak1, which share 32% amino acid identity across the kinase domain but otherwise differ in sequence and domain structure, and then test the contributions of various domains for protein localization, complementation of mutants, and activation of signaling. We found that overexpression of the wild-type kinases stimulated JNK signaling in alternate contexts, so cells were capable of responding to both MAP3Ks, but with distinct outcomes. Relative to wild-type, the catalytic domain swaps compensated weakly or not at all, despite having a shared substrate, the JNK kinase Hep. Tak1 C-terminal domain-containing constructs were inhibitory in Tak1 signaling contexts, including tumor necrosis factor-dependent cell death and innate immune signaling; however, depressing antimicrobial gene expression did not necessarily cause phenotypic susceptibility to infection. These same constructs were neutral in the context of Slpr-dependent developmental signaling, reflecting differential subcellular protein localization and by inference, point of activation. Altogether, our findings suggest that the selective deployment of a particular MAP3K can be attributed in part to its inherent sequence differences, cellular localization, and binding partner availability.